2021
DOI: 10.1016/j.jopan.2020.06.024
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Noise Levels in the Operating Room on the Stress Levels and Workload of the Operating Room Team

Abstract: The research was conducted to evaluate the noise levels and the effect of noise on the workload and stress levels of the operating room (OR) staff of a public hospital. Design: Descriptive and cross-sectional study. Methods: The data were obtained by measuring ambient noise during 403 orthopaedic, urological, and general surgeries on weekdays between July and October 2019. We measured the noise by dividing the surgery into three phases. These phases are as follows: from the entry of the patient, induction of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…It is generally believed that demographic factors, social psychological factors, and personality are related to occupational stress (15,19), while excessive workload, task conflicts, and exposure to occupational hazards in the workplace are risk factors for stress (18,41,42). In this study, we found that personality, psychological flexibility, and role overload were associated with PSY and PHS among the medical staff.…”
Section: Discussionmentioning
confidence: 53%
“…It is generally believed that demographic factors, social psychological factors, and personality are related to occupational stress (15,19), while excessive workload, task conflicts, and exposure to occupational hazards in the workplace are risk factors for stress (18,41,42). In this study, we found that personality, psychological flexibility, and role overload were associated with PSY and PHS among the medical staff.…”
Section: Discussionmentioning
confidence: 53%
“…Other contributory factors are assignment of too many responsibilities to one individual, workplace ergonomics, such as noise, too much reliance on paperwork for communication, and preoccupation with the main purpose of professional communications, i.e., caring for patients, at the cost of the other aspects of professional communications, including consulting others, transferring experiences, professional training, and teamwork. According to Bellandi (2018), physicians and nurses spend a large amount of their time filling out forms in hospitals [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Occupational noise annoyance has been significantly related to mental health, including depressive symptoms and suicidal ideation [ 24 ]. In a study of the effects of noise on the workload and stress levels of operating room staff, anxiety and workload scores were positively correlated with noise levels [ 25 ]. Noise is also one of the occupational hazards affecting job stress [ 26 ].…”
Section: Introductionmentioning
confidence: 99%